Structural and magnetic characterization of Ni(ii), Co(ii), and Fe(ii) binuclear complexes on a bis(pyridyl-triazolyl)alkane basis. Issue 28 (24th June 2019) - Gusev, Alexey; Nemec, Ivan; Herchel, Radovan; Riush, Irina; Titiš, Ján; Boča, Roman; Lyssenko, Konstantin; Kiskin, Mikhail; Eremenko, Igor; Linert, Wolfgang
Abstract : Reactions of bis[5-(2-pyridyl)-1, 2, 4-triazol-3-yl]alkanes (alkane spacers –(CH2 ) n –: n = 2 in L2, n = 3 in L3, − n = 4 in L4) with Ni, Co, Fe salts resulted in the preparation of five series of mononuclear and binuclear complexes. Abstract : Reactions of bis[5-(2-pyridyl)-1, 2, 4-triazol-3-yl]alkanes (alkane spacers = –CH2 – in L2, –C3 H6 – in L3, –C4 H8 – in L4) with M(ii )A2 salts (M = Ni, Co, Fe) resulted in the preparation of five series of mononuclear ([M(L2)(H2 O)2 ] 2+, 1a–c ) or binuclear ([M2 (L3)2 (H2 O)4 ] 4+, 2a–c ; ([M2 (L4)2 (H2 O)4 ] 4+, 3a–c, [M2 (L3)2 (μ-ox)] 2+, 4a–c ; [M2 (L4)2 (μ-ox)] 2+, 5a–c ) complexes. The crystal structures of ten complexes were determined by single-crystal X-ray crystallography. Magnetic properties of the compounds were characterized by SQUID magnetometry and were analyzed by fitting on a spin Hamiltonian model. It was revealed that Fe(ii ) and Co(ii ) compounds exhibit non-negligible anisotropy and in the case of2a–c and3a–c complexes weak ferromagnetic interactions between the metal centers were observed. In the case of complexes containing an M2 (μ-ox) 2+ core strong antiferromagnetic interactions were observed within the dimer. Remarkably, solid state luminescence of Co(ii ) and Fe(ii ) complexes (1b, 2b, 3b and1c, 2c, 3c ) was observed.